Impact of vegetarian versus non-vegetarian diet on health outcomes in male individuals: A comparative study. Issue 1 (March 2023) - Pattar, Spurti; Shetty, Prashanth; Shetty, Geetha B.
Abstract: Background: Vegetarianism versus non-vegetarianism is a perfect example of an opposing view of a healthy diet. Vegetarians consume plant-based foods whereas non-vegetarians consume animal-based foods. Aims and objectives: This study aimed to evaluate and compare the impact of vegetarian and non-vegetarian diets on different health outcomes such as anthropometric measurements, sleep quality, and mindfulness in male individuals of ages 16–25 years. Materials and methods: Sixty subjects were recruited from two different hostels. The total subjects were divided into two groups i.e., vegetarian group (n = 30) was fed a vegetarian diet and non-vegetarian group (n = 30) was fed a non-vegetarian diet for 3 months. The subjects were assessed for anthropometry, PSQI scoring, and mindfulness at baseline and after three months. Results: On comparison of variables between the two groups, a significant difference has been observed. In the comparison of anthropometric data, there was a significant difference in BMI (p < 0.001) between the groups. PSQI scores showed a significant difference between the groups with mean global scores: group 1: 3.03 ± 2.5; group 2: 5.14 ± 2.23. Mindful eating among vegetarians was significant (p < 0.001). Conclusion: A vegetarian diet had a positive impact on health outcomes compared to a non-vegetarian diet.